Merging company culture: Marriott and Ritz-Carlton - Steinbock, Erich (Henry Stewart Talks, 2024)
This case study discusses the merger of Marriott and Ritz-Carlton, illustrating the importance of giving company culture due consideration in devising a merger strategy.